Spermatological characters of bothriocephalideans (Cestoda) inferred from an ultrastructural study on Oncodiscus sauridae and Senga sp - Sípková, Lenka; Levron, Céline; Oros, Mikuláš; Justine, Jean-Lou (Parasitology research, 2011)
Spermiogenesis and ultrastructure of the spermatozoon of two bothriocephalidean cestodes, Oncodiscus sauridae from the lizardfish Saurida nebulosa Valenciennes, 1850 and Senga sp. from the eel Mastacembelus armatus (Lacepède, 1800), have been studied using transmission electron microscopy. Spermiogenesis included the formation of a zone of differentiation, where two centrioles associated with the striated rootlets occur. An intercentriolar body composed of one thick central electron-dense plate and two thinner plates on each side appears between two centrioles. Two flagella of unequal length grow and undergo a vertical rotation and proximodistal fusion with the median cytoplasmic process. Subsequently, the nucleus penetrates into the median cytoplasmic extension. The electron-dense material in the early stages of spermiogenesis is characteristic for the apical region of the differentiation zone. This electron-dense material is typical for basal tapeworms, e.g., Bothriocephalidea, Caryophyllidea, Diphyllobothriidea, and Spathebothriidea. The mature spermatozoon of O. sauridae and Senga sp. is filiform and possesses two axonemes of the 9 + "1" trepaxonematan pattern, a nucleus, cortical microtubules, and electron-dense granules. The anterior part of the gamete contains a single electron-dense crested body. The most interesting character found is the presence of a ring of cortical microtubules encircling the axoneme in the anterior part of the spermatozoon. This feature has been detected only for species of the order Bothriocephalidea and may represent a synapomorphy of these tapeworms. A classical pattern for spermatological characters (spermiogenesis of type I with dense material in early stages and sperm of type II with a characteristic ring of cortical microtubules in the anterior part) in Bothriocephalidea is discussed.
Keywords: transmisní elektronová mikroskopie; Chordata; Microscopy, Electron, Transmission; Spermatozoa; Animals; organely; spermie; Spermatogenesis; mužské pohlaví; Male; zvířata; Organelles; spermatogeneze; Cestoda